2004
DOI: 10.2134/jeq2004.1540
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Biodegradability of Sludge Bacterial Extracellular Polymers in Soil and Their Influence on Soil Copper Behavior

Abstract: Bacterial extracellular polymers (BEP) affect the translocation and fate of organic and inorganic pollutants in terrestrial and aquatic ecosystems. In this study, BEP from activated sludge was compared with sludge dissolved organic matter (DOM) in terms of behavior and effects on the mobilization and bioavailability of Cu in a well-aged Cu-contaminated orchard sandy loam. Addition of sludge BEP (10-200 mg dissolved organic carbon [DOC] L(-1)) to the soil resulted in 1.6- to 12.8-fold-higher soil soluble Cu con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Broos and others (2004) soil resulted in several-fold higher soluble Cu concentration, and also increased Cu uptake by ryegrass grown in the soil. They suggested that these may be attributed to less sorption of BEP by soil, slow degradation, and higher affinity with Cu, and advised that the environmental risk of Cu should receive more attention if BEP is added to soils (Zhou et al, 2004b). Weggler and others (2004) report that increasing chloride (Cl) concentration in soil solution has been shown to increase Cd concentration in soil solution and Cd uptake by plants, when grown in phosphate fertilizer-or biosolid-amended soils.…”
Section: Adams and Coworkersmentioning
confidence: 99%
“…Broos and others (2004) soil resulted in several-fold higher soluble Cu concentration, and also increased Cu uptake by ryegrass grown in the soil. They suggested that these may be attributed to less sorption of BEP by soil, slow degradation, and higher affinity with Cu, and advised that the environmental risk of Cu should receive more attention if BEP is added to soils (Zhou et al, 2004b). Weggler and others (2004) report that increasing chloride (Cl) concentration in soil solution has been shown to increase Cd concentration in soil solution and Cd uptake by plants, when grown in phosphate fertilizer-or biosolid-amended soils.…”
Section: Adams and Coworkersmentioning
confidence: 99%
“…Investigations have revealed that the presence of DOM in soil can facilitate mobility and transport of heavy metals, acting as "transporter" through the formation of soluble metal-organic complexes (Temminghoff et al 1997, Zhou et al 2004, Li and Zhou 2010. Thus, the application of organic materials such as manures, compost, and sewage sludge improves the physicochemical and biological conditions of the soil; however, DOM present in these wastes can affect speciation, transformation and the behavior of heavy metals in the environment (Benedetti et al 1996).…”
Section: Introductionmentioning
confidence: 99%